Evaluating the environmental effects of transportation modes using an integrated methodology and an application - Tuzkaya, U. R. (SPRINGER, 2009)
The increasing needs for transportation of freight and passengers causes environmental impacts. Preventing studies for these impacts should be considered by logistics Firms and encouraged by the regulations of authorities. An important contribution can be provided by determining the environmental effects of the transportation modes in specific regions and using the most convenient ones. In this study, multiple criteria decision-making techniques, including human judgments, tangible and intangible criteria and priorities are used. Fuzzy analytic hierarchy process and preference ranking organization method for enrichment evaluation, as two of the multi criteria decision-making methodologies, are integrated for ranking the transportation modes in terms of the environmental effects of them. The proposed decision-making process is applied to chose the environmentally convenient transportation mode with respect to the determined evaluation criteria in Marmara Region of Turkey. The results indicate that, the main problem for the Marmara Region about transportation aspects is to pass from the intensive utilization of the road transportation mode to another one. In this study it is seen that the most convenient transformation mode in Marmara Region is the sea transportation mode.
Keywords: Decision-making techniques; transportation modes; multi criteria decision-making; fuzzy approach; MULTICRITERIA DECISION-MAKING; ANALYTIC HIERARCHY PROCESS; EXTENT ANALYSIS METHOD; FUZZY AHP; PROMETHEE; SELECTION; SYSTEMS; Environmental Sciences & Ecology